Role of HR in strengthening cyber security on the social media platform of the Teratai Putih Foundation, Yogyakarta - Idam Wahyudi; Anggun Sulistyowati; Bikorin Bikorin (Universitas Pendidikan Indonesia, 2025)
In the increasingly advanced digital era, social media has become a primary tool for organizations, including Yayasan Teratai Putih Yogyakarta, to disseminate information, build networks, and enhance community engagement. As an institution engaged in social and educational activities, the foundation heavily relies on social media to implement various programs and social campaigns. However, alongside the benefits it offers, there are significant cybersecurity challenges that must be taken seriously. This community service program (Abdimas) aims to enhance the capacity and awareness of human resources (HR) at Yayasan Teratai Putih Yogyakarta in strengthening cybersecurity on the social media platforms they manage. The target participants of this initiative include social media administrators of the foundation, including staff and volunteers responsible for information management and digital interactions. As a result of this socialization activity, participants gained an in-depth understanding of data protection strategies, security policies, and preventive measures against cyber threats. With increased awareness and skills in managing digital security, the foundation can minimize the risk of cyberattacks while maintaining its credibility and public trust in the information it shares. Abstrak Dalam era digital yang semakin maju, media sosial telah menjadi alat utama bagi organisasi, termasuk Yayasan Teratai Putih Yogyakarta, untuk menyebarkan informasi, membangun jejaring, dan meningkatkan keterlibatan masyarakat. Sebagai lembaga yang bergerak di bidang sosial dan pendidikan, yayasan ini sangat bergantung pada media sosial untuk menjalankan berbagai program dan kampanye sosial. Namun, di balik manfaat yang ditawarkan, terdapat tantangan besar dalam hal keamanan siber yang harus diperhatikan secara serius. Kegiatan pengabdian kepada masyarakat (Abdimas) ini bertujuan untuk meningkatkan kapasitas dan kesadaran Sumber Daya Manusia (SDM) di Yayasan Teratai Putih Yogyakarta dalam memperkuat keamanan siber pada platform media sosial yang mereka kelola. Sasaran kegiatan ini adalah pengelola media sosial Yayasan Teratai Putih Yogyakarta, termasuk staf dan relawan yang bertanggung jawab atas pengelolaan informasi serta interaksi digital. Hasil dari kegiatan sosialisasi ini peserta memperoleh pemahaman mendalam mengenai strategi perlindungan data, kebijakan keamanan, serta langkah-langkah pencegahan ancaman siber. Dengan meningkatnya kesadaran dan keterampilan dalam mengelola keamanan digital, yayasan dapat meminimalkan risiko serangan siber serta menjaga kredibilitas dan kepercayaan publik terhadap informasi yang disampaikan. Kata Kunci: Era digital; keamanan siber; manajemen sumber daya manusia